Toxicity and Oxidative Stress Biomarkers in the Organs of Mice Treated with Mesoporous Polydopamine Nanoparticles Modified with Iron and Coated with Cancer Cell Membrane - Szukalska M; Grześkowiak BF; Bigaj-Józefowska MJ; Witkowska M; Cicha E; Sujka-Kordowska P; Miechowicz I; Nowicki M; Mrówczyński R; Florek E (International Journal of Nanomedicine)
Marta Szukalska,1 Bartosz F Grześkowiak,2 Magdalena J Bigaj-Józefowska,2 Marta Witkowska,3,4 Emilia Cicha,5 Patrycja Sujka-Kordowska,6 Izabela Miechowicz,7 Michał Nowicki,6 Radosław Mrówczyński,3,4 Ewa Florek1 1Laboratory of Environmental Research, Department of Toxicology, Poznan University of Medical Sciences, Poznań, Poland; 2NanoBioMedical Centre, Adam Mickiewicz University, Poznań, Poland; 3Faculty of Chemistry, Adam Mickiewicz University, Poznań, Poland; 4Centre for Advanced Technologies, Adam Mickiewicz University, Poznań, Poland; 5Laboratory of Experimental Animals, Poznan University of Medical Sciences, Poznań, Poland; 6Department of Histology and Embryology, Poznan University of Medical Sciences, Poznań, Poland; 7Department of Computer Science and Statistics, Poznan University of Medical Sciences, Poznań, PolandCorrespondence: Marta Szukalska, Laboratory of Environmental Research, Department of Toxicology, Poznan University of Medical Sciences, Rokietnicka 3 Street, Poznan, 60-806, Poland, Email martan@ump.edu.plPurpose: Polydopamine nanoparticles (PDA NPs) have great potential in medicine. Their applications being widely investigated in cancer therapy, imaging, chemotherapy, photodynamic therapy (PDT), photothermal therapy (PTT), and tissue repair. The aim of our study was to assess the in vivo toxicity and changes in oxidative stress biomarkers in organs of animals treated with mesoporous PDA NPs modified with iron (MPDAFe NPs), coated with the cancer cell membrane and loaded with doxorubicin (DOX), and subsequently subjected to PTT.Methods: Liver and kidney homogenates were obtained from BALB/c nude mice with xenograft HepG2 human hepatoma cells, treated with iron modified mesoporous PDA nanoparticles, coated with the cancer cell membrane and loaded with doxorubicin (MPDAFe@DOX@Mem NPs), and subjected to PTT. These samples were used for histological evaluation and measurement of oxidative stress biomarkers, including total protein (TP), reduced glutathione (GSH), nitric oxide (NO), S-nitrosothiols (RSNO), thiobarbituric acid reactive substances (TBARS), trolox equivalent antioxidant capacity (TEAC), catalase (CAT), glutathione S-transferase (GST), and superoxide dismutase (SOD).Results: In the kidney, MPDAFe@DOX@Mem NPs in combination with PTT increased GSH (43%), TBARS (32%), and CAT (27%), while SOD decreased by 20% compared to the control group. Additionally, CAT activity in the liver increased by 79%.Conclusion: Significant differences in oxidative stress parameters and histological changes after administration with MPDAFe@DOX@Mem NPs and PTT were observed in the kidneys, showing more pronounced changes than the liver, indicating potential kidney toxicity. Our research provides insights into oxidative stress and possible toxic effects after in vivo administration of mesoporous PDA NPs combined with chemotherapy-photothermal therapy (CT-PTT), which is extremely important for their future applications in anticancer therapies. Keywords: polydopamine nanoparticles, oxidative stress, liver cancer model, in vivo toxicity, chemo- and photothermal therapy